Identifikasi Kontaminasi Soil Transmitted Helminth (STH) pada Sayuran Selada (Lactuca sativa) dan Kubis (Brassica oleracea) di Pasar Tradisional Kota Medan - Sarumaha, Kartika Ivanna Putri (Universitas HKBP Nommensen, 2025)
Background: Soil-transmitted helminths (STH) eggs/larvae have various ways to enter the human body, such as when children play without wearing shoes on soil contaminated with STH eggs/larvae, water contaminated with STH eggs, and by attaching eggs/larvae to raw vegetables consumed directly without thorough washing and cooking. Objective: Identifying Soil Transmitted Helminth (STH) contamination in lettuce (Lactuca sativa) and cabbage (Brassica oleracea) through the sedimentation method. Methods: This research is of a descriptive observational type with a cross-sectional design. The sampling technique involves cluster random sampling method, with samples collected from 10 markets in 10 districts of Medan city. The total samples for lettuce (Lactuca sativa) and cabbage (Brassica oleracea) are each 70 samples. Results: The results of STH contamination in lettuce (Lactuca sativa) is Hookworm eggs/larvae in 11 samples (64.71%), A. lumbricoides eggs in three samples (17,65%), and T. trichiura eggs in three samples (17.65%). STH contamination in cabbage (Brassica oleracea) is Hookworm eggs/larvae in four samples (40%), A. lumbricoides eggs in four samples (40%), and Trichuris trichiura eggs in two samples (20%). The highest STH contamination across all research locations is found in Pajak Pagi Market 5, with six samples of lettuce (85.71%) and two samples of cabbage (28.57%), followed by Pringgan Market with four samples of lettuce (57.14%) and two samples of cabbage (28.57%). Conclusion: In research, the most prevalent STH contaminant is Hookworm larvae in both lettuce (Lactuca sativa) and cabbage (Brassica oleracea).